Peripheral blood transcriptome profiling enables monitoring disease progression in dystrophic mice and patients. Issue 4 (10th March 2021) - Signorelli, Mirko; Ebrahimpoor, Mitra; Veth, Olga; Hettne, Kristina; Verwey, Nisha; García‐Rodríguez, Raquel; Tanganyika‐deWinter, Christa L; Lopez Hernandez, Luz B; Escobar Cedillo, Rosa; Gómez Díaz, Benjamín; Magnusson, Olafur T; Mei, Hailiang; et al.
Abstract: DMD is a rare disorder characterized by progressive muscle degeneration and premature death. Therapy development is delayed by difficulties to monitor efficacy non‐invasively in clinical trials. In this study, we used RNA‐sequencing to describe the pathophysiological changes in skeletal muscle of 3 dystrophic mouse models. We show how dystrophic changes in muscle are reflected in blood by analyzing paired muscle and blood samples. Analysis of repeated blood measurements followed the dystrophic signature at five equally spaced time points over a period of seven months. Treatment with two antisense drugs harboring different levels of dystrophin recovery identified genes associated with safety and efficacy. Evaluation of the blood gene expression in a cohort of DMD patients enabled the comparison between preclinical models and patients, and the identification of genes associated with physical performance, treatment with corticosteroids and body measures. The presented results provide evidence that blood RNA‐sequencing can serve as a tool to evaluate disease progression in dystrophic mice and patients, as well as to monitor response to (dystrophin‐restoring) therapies in preclinical drug development and in clinical trials. Synopsis: This study explored the potential of RNA‐sequencing of peripheral blood to track non‐invasively disease progression and response to treatment in dystrophic mice and in patients affected by Duchenne Muscular Dystrophy (DMD). The analysis of paired muscle and blood samples from healthy and dystrophic mice led to the identification of a large number of genes that are differentially expressed in muscle and showed that the muscle signature is partly reflected in blood. Treatment with two different antisense drugs, that yield different levels of dystrophin restoration, led to the identification of 14 genes whose expression in blood is associated with the safety and efficacy of treatment with antisense nucleotide drugs. The study of gene expression in patients affected by DMD showed the presence of a strong disease signature in blood. Comparison of the results on blood gene expression in mice and humans led to the identification of 688 genes that are differentially expressed both in dystrophic mice and in DMD patients. Abstract : This study explored the potential of RNA‐sequencing of peripheral blood to track non‐invasively disease progression and response to treatment in dystrophic mice and in patients affected by Duchenne Muscular Dystrophy (DMD).